Empowered learner: matching student personality with different learning preferences - Liew, Lee Min *; Fazilah Ramzan, * (Sunway College Kuala Lumpur, 2015)
The aim of this study is to identify students’ personality types with their learning preferences for different Pre- University programmes in Sunway College Johor Bahru. It is important to acknowledge students’ learning preferences by using an effective teaching method in order to enhance students’ learning curve. This paper will first identify the characteristics of students’ personalities through the use of Myers Briggs Type Indicator (MBTI). Thereafter, the common personality types among Pre-University students will be recognised to match their preferred learning style. Through a review of related studies, this paper aims to shed some light on matching students’ personalities with their learning preferences so as to design a more effective teaching method.